La modalidad de educación virtual para estudiantes con necesidades educativas especiales en covid-19, centro educativo el Ángel, Loja, 2020–2021. - Martínez Silva, Diana Carolina (2022)
Currently, the Covid-19 pandemic has caused a blow and transformation throughout the world, which forced face-to-face institutions to become distance educators. In their eagerness to guarantee the continuity of education, educational centers faced new risks and challenges related to the emerging modality of virtual teaching, for students with special educational needs (SEN), a highly vulnerable group. Against this background, this research aims to contribute to the full description of this problem in relation to SEN, and glimpse some guidelines for inclusive digital education in this framework. The general objective of this research work was to evaluate the strategies of virtual education for students with SEN in Covid-19, within the El Ángel Educational Center. For this, the methodology corresponds to a mixed explanatory sequential research approach, having a descriptive scope that includes documentary review, application of surveys and execution of interviews. Regarding the application of surveys, nineteen teachers and seventy-five parents of the El Ángel Educational Center participated, while the interviews consisted of semi-structured instruments to focus groups with a director, two teachers, two parents and a student. to know the perceptions of the population under study. According to the results obtained in the investigation, it was evidenced that there is no adequate diagnosis of the information by the teachers around the preparation of their virtual classes. Likewise, the lack of training in the context of the new virtual modality became evident, especially towards competitions for more dynamic and interactive classes. On the other hand, the management of the platforms by the parents must be strengthened, the lack of follow-up and articulated accompaniment to the students of the teachers with the representatives, and the limited success in the learning results, due to the lack of innovative methodological strategies. Regarding the diagnosis, an alternative proposal for virtual education was developed on activities to encourage learning, according to the context and requirements of students with SEN, teachers and representatives of the El Ángel Educational Center in the city of Loja. The viability of this alternative proposal is concluded, but above all the need to implement duly structured strategies according to the specific needs and requirements of students with SEN, so that teachers have adequate and relevant methodological strategies that allow having a variety of resources and activities to provide quality learning experiences in that student sector.